Knowledge on obstetric danger signs among antenatal mothers attending a tertiary level hospital, Nepal - Thapa, Binu; Manandhar, Krishnaa (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: All pregnant women are at risk and can face problems at any time during or following pregnancy and childbirth which can cause death of mothers. Knowledge of key danger signs is essential for motivating women to seek skilled attendance at birth and also to seek referral in case of complications which definitely improves health of the mother and newborns. This study aimed to assess pregnant womens’ knowledge about obstetric danger signs and its associated factors. Materials & Methods: Quantitative approach with a facility based cross-sectional study was conducted among pregnant mothers attending Anti Natal Clinic of Dhulikhel hospital, Nepal. Data was collected from 1st June to 25th June 2017. Sampling technique was non probability, purposive sampling technique. A standardized tool was adopted. Face to face interview technique was used. Data had been processed by SPSS 20 version then analyzed using descriptive as well as inferential statistic. Results: Two third of the respondents (66.0%) had adequate knowledge on obstetric danger signs, while 21.0% of respondents had inadequate knowledge and few respondents (13.0%) had moderate knowledge on that. Age, educational status and gravida were not significantly associated with knowledge on obstetric danger signs but occupation and trimester of pregnancy were found to be associated with the same. Conclusion: A significant proportion of pregnant women do not have adequate knowledge on obstetric danger signs. Therefore, the quality of health information about obstetric danger signs during ANC follow up is to be improved.